2005
DOI: 10.1002/jcc.20184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of clustered DNA damage sites containing 8‐oxoguanine and abasic site

Abstract: Clustered DNA damage sites induced by ionizing radiation have been suggested to have serious consequences to organisms, such as cancer, due to their reduced probability to be repaired by the enzymatic repair machinery of the cell. Although experimental results have revealed that clustered DNA damage sites effectively retard the efficient function of repair enzymes, it remains unclear as to what particular factors influence this retardation. In this study, approaches based on molecular dynamics (MD) simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The network within the nodes is of DTU (Data Transfer Unit) type with a maximum speed of 4 GB/s × 2. The optimal number of CPUs when running the parallel MPI version of SANDER was found to equal 32 [16], because the speed-up is only marginal when the number of CPUs is increased further, and because the scaling properties are also slightly dependent on the type of simulated system. The main bottleneck in our system might come from an imbalance of the speeds on CPU-to-CPU communications, which is a major problem for most MPI coded programs, mainly caused by slow crosscommunication among nodes due to the data transfer technique applied in the network connecting them with each other, even if the communication within the node is fast, which is usually done by memory-copying.…”
Section: Molecular Dynamics Protocolmentioning
confidence: 99%
“…The network within the nodes is of DTU (Data Transfer Unit) type with a maximum speed of 4 GB/s × 2. The optimal number of CPUs when running the parallel MPI version of SANDER was found to equal 32 [16], because the speed-up is only marginal when the number of CPUs is increased further, and because the scaling properties are also slightly dependent on the type of simulated system. The main bottleneck in our system might come from an imbalance of the speeds on CPU-to-CPU communications, which is a major problem for most MPI coded programs, mainly caused by slow crosscommunication among nodes due to the data transfer technique applied in the network connecting them with each other, even if the communication within the node is fast, which is usually done by memory-copying.…”
Section: Molecular Dynamics Protocolmentioning
confidence: 99%
“…Many evidence clearly demonstrated that complex DNA lesions are more dif2icult for the cellular machinery to repair than are individual damage sites (28)(29)(30)(31)(32)(33) . With synthetic oligonucleotides containing several types of DNA damage, David-Cordonnier et al demonstrated that the ef2iciency of incision of an AP site within a region of clustered DNA damage is signi2icantly reduced by the presence of a second AP site or SSB (28) .…”
Section: The Biological Effects Of Hze Particlementioning
confidence: 99%
“…The spatial distribution of different types of lesions within the clustered DNA damage and the physical location of damage within nuclear subdomains (euchromatic or heterochromatic) might in2luence the cellular ability to repair complex DNA damage. Approaches based on molecular dynamics (MD) simulation have been applied to examine conformational changes and energetic properties of DNA molecules containing clustered damage sites with a basic or 8-OxoG, the results showed that DNA molecules containing a clustered damage site develops speci2ic characteristic features: sharp bending at the lesioned site and weakening or complete loss of electrostatic interaction energy between 8-oxoG and bases located on the complementary strand (33) . These conformations may make it dif2icult for repair enzymes to bind to the region.…”
Section: The Biological Effects Of Hze Particlementioning
confidence: 99%
“…Nunez et al calculated the vibrations in human purine nucleoside phosphorylase (hPNP) by MD method and hybrid quantum mechanical/molecular mechanical method [8] , but they only gave the intramolecular frequencies of hPNP. Fujimoto et al used MD to study the clustered DNA damage sites containing 8-oxoguanine and abasic site [9] . Yamaguchi et al studied single strand broken DNA by MD [10] .…”
Section: Introductionmentioning
confidence: 99%